Investigation of Calnexn Protein Expression in Imatinib Sensitive and Resistant K562 Cells - Arzu Z. Karabay (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim:The aim of this study is to determine the expression levels of endoplasmic reticulum (ER) chaperon protein calnexin in K562 cell line which is the cell line model of chronic myeloid leukemia characterised with the transformation of numerous blood stem cells into abnormal granulocytes. Calnexin levels in K562 cells and its resistant counterpart (K562R) to Imatinib, the first line therapy option for CML were examined. In addition, effects of first and second generation tyrosine kinase inhibitors, Imatinib and Nilotinib on calnexin levels and cell viability parameters in K562S and K562R cells were also determined.Material and Method:In this study, K562S (sensitive to Imatinib) cell line, which is the cell model of the blast phase of CML, and K562R cell lines, which are resistant to imatinib (5uM), were used. Cells were cultured in parallel. K562S cells treated with or without 0.5 uM imatinib and 0.05 uM Nilotinib and K562R cells treated with or without 20 uM Imatinib and 0.1 uM Nilotinib were collected 48 hours after treatment and cell viability, apoptosis, cell morphology and calnexin protein expression were determined with MTT assay, flow cytometry, light microscopy and western blot respectively.Results and conclusion:In this study, it was shown that the total cellular expression of calnexin, a chaperone that regulates the folding of proteins in the endoplasmic reticulum, did not show any significant difference between the K562S and K562R cells, On the other hand, since Imatinib and Nilotinib significantly decreased calnexin protein expression in K562S cells and did not show any significant effect on K562R cells, this may indicate that the ER stress pathway and possibly calnexin are involved in the action mechanisms of these drugs. Therefore, even if no significant difference in calnexin levels was found between K562R and K562S cells, there may be differences in the ER stress pathway between the sensitive and resistant cells. For further studies, it is suggested to investigate the distribution of calnexin in different intracellular compartments as well as its modulation with drugs.